Review Paper on the Methodological Choice for Assessing the Economic Contribution of Pilgrimage Site - Bhatt, Shankar Datt; Subedi, Khem Raj; Dwivedi, Ruchi (The Management Review, 2025)
Pilgrimage sites attract millions of people worldwide, driven by religious faith, and significantly stimulate economic activities. These sites create employment opportunities for hundreds of thousands people around the world, generate substantial income, and positively impact local business growth, contributing to overall economic prosperity and revitalization but remain in shadow in the absence of rigorous theoretical discussion to adopt appropriate methodologies to capture these aspects. This paper provides a precise theoretical and empirical review of literature on measuring the economic contribution of pilgrimage tourism around the world. It aims to deepen understanding of the theoretical underpinnings and empirical practices to explore potentiality of using Individual Travel Cost Method under revealed preference techniques to measure the economic contribution made by popular pilgrimage sites on national economy. In this context, the literatures for this review was traced from peer-reviewed journal articles, conference proceedings, books, and research reports that address the economic impact of pilgrimage tourism around the world. The key economic dimensions and indicators include visitors' satisfaction, consumers' satisfaction, employment generation, and local business growth.